DESCRIPTION OF THE UNDERSTANDING AND CONCERN OF CHILDREN WITH SPECIAL NEEDS FOR EAR HYGIENE, EAR INFECTION AND HEARING HEALTH AT GOVERNMENT SPECIAL SCHOOL II BANJARMASIN - Kurniadi, Melody Audria (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Children with special needs often lack good knowledge about health. In addition, ear and hearing health is often neglected by society. Ear and hearing disorders can cause disability or limitations in socializing and can also cause serious complications. The aim of this study is to provide an overview of the level of understanding and concern for ear health and hearing health. The number of samples was 37 people with an age range of 11-18 years with a cross-sectional study. The research was conducted descriptively by using a questionnaire containing 18 questions. The results of this study showed that all research subjects did not understand the correct habit of cleaning their ears. Most of the subjects did not understand the causes of ear infections. The most commonly recognized symptom of an ear infection is ear pain (54%). Almost all participants understand that ear infections can have complications in the brain. The use of earphones (40%) is not a habit for the subject. More than 50% of subjects have an understanding that hearing loss can be cured. Almost all (97%) of respondents felt the need to get more information about ear and hearing health. Understanding of ear and hearing health in children in special needs is still relatively low. The level of children in special needs 's concern for ear and hearing health is also still low. Government Special School II Banjarmasin students feel they need information related to ear and hearing health.